Los determinantes del trabajo a tiempo parcial en Lima Metropolitana - Saavedra Martinez, Manuel Enrique (2011)
The following paper examines the part-time work in Metropolitan Lima in 2008. The overall objective is to identify the determinants of the incidence of part-time work in Lima. We worked with one Probit econometric model, measured by the National Survey of Households (NSH), which explores the job characteristics of people. This will determine the presence of part-time workers in the areas of trade, health, education and communication; also realized that this group has completed university studies and incomplete, and the woman has a probability of 83,11397% more than men of working part time.